Analisis faktor-faktor penyebab ketimpangan pendapatan di provinsi D.I.Yogyakarta (periode 2005-2021) - Farah Hanieva Alfadhillah; Nadia Nur Windari; Mirda Nurparida; Muhammad Affan Widyarif (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
This study aims to examine the effect of HDI, APS, and the Minimum Wage on the high level of income inequality in DI Yogyakarta Province. DI Yogyakarta province, which is often dubbed the center of education, is evidenced by the highest HDI and NER on the island of Java, which has the highest inequality in Indonesia. The method used in this study is a descriptive method with a quantitative approach, namely using multiple regression analysis methods with OLS (Ordinary Least Square) estimator and classical assumption test analysis tool. The data used are secondary data obtained from official sources such as BPS and other official agencies. Data collection techniques using literature study. The results showed that HDI had no effect on Income Inequality. The APS variable has a significant effect on Income Inequality and the Minimum Wage has an effect on Income Inequality in the Province of DI Yogyakarta in 2005-2021.